Effects of MOTOmed® movement therapy on the motor function and main symptoms of patients with Parkinson’s disease: a systematic review - Karina Pitombeira Pereira-Pedro; Iris Machado de Oliveira; José María Cancela Carral; Irimia Mollinedo Cardalda (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Scientific findings show immediate improvements after forced assisted cycling at high pedaling speeds of up to 90 revolutions per minute in patients with Parkinson's Disease, thus this review aimed to estimate the efficacy of MOTOmed® movement therapy. to increase motor function and alleviate the main symptoms in these patients. Methods: Systematic review including randomized controlled trials examining MOTOmed®  movement therapy interventions, alone or as an adjunct to rehabilitation, for patients with Parkinson's disease. The risk of bias assessment tool followed the recommendations of the Cochrane Handbook 5.1.0. All included studies reported the effects of mobility as primary outcomes. Standardized mean differences or mean differences with corresponding 95% confidence intervals (CI) were calculated. Results: In total, 7 trials with a total of 206 patients were included in the analysis. All studies were of moderate quality. MOTOmed®  movement therapy resulted in statistically significant improvements in the MDS-UPDRS (Movement Disorder Society-Unified Parkinson Disease Rating Scale) Motor III score (p<0.05); Upper limb MDS-UPDRS score (p<0.05); Total MDS-UPDRS (p<0.04): Upper body function (p<0.007); bradykinesia (p<0.044); Cycling variables: higher cadence (p<0.001); Timed up and done (p>0.05); tremor score (p<0.05); Walking time (p<0.05); Gait steps (p<0.05); Pronation and supination (p<0.05); Parkinson's Disease Questionnaire -PQD8 (bandages and depressions p<0.05); Gait analysis: speed (p<0.000), stride length (p<0.000), monopedal posture (p<0.000), swing phase (p<0.000); Biodex® Balance System: Clinical Test of Sensory Integration of Balance-CTSIB1 (p<0.007). Conclusion: MOTOmed®  movement therapy alone or combined with standard rehabilitation improves motor function and main symptoms in patients with Parkinson's disease.